Exploring the Impact of Paternal B12 Levels During the Periconceptional Period on IUI Success - Atea, Mouroge Khalaf; Al-Anbari, Laith Amer (South Eastern European Journal of Public Health, 2024)
Background: The present study is a novel exploration of the effects of vitamin B12 supplementation on seminal fluid parameters and the outcomes of intrauterine insemination (IUI). Specifically, we aimed to evaluate the concentrations of vitamin B12 in blood and seminal plasma before and after two months of supplementation. Objectives: investigate the effects of vitamin B12 supplementation on the characteristics of seminal fluid parameters and IUI outcomes. Material and Methods: A randomized controlled experiment with 100 randomly selected infertile couples. The patients were divided into two equal groups according to their vitamin B12 dosage. Group A consists of 50 couples who are taking B12 supplements. Obtain blood and seminal plasma samples from couples to measure the level of vitamin B12. Group B consists of 50 couples and does not include any supplements. The couples in group B initiated ovulation induction and intrauterine insemination (IUI) during the same month as the medical examination without the use of any additional supplements. Still, after two months of vitamin B12 supplement, group A started ovulation induction. Result: Basal semen parameters for sperm count, sperm motility in grades, and sperm morphology in the study group have a higher sperm count than the control group. Vitamin B12 intake for two months improves sperm morphology and increases sperm motility in grades A and B, according to the current study. This has a favorable effect on sperm count overall. Conclusion: research will determine the positive effect of vitamin B12 supplements on sperm parameters and IUI results.